Ultrasound scattering in cancellous bone - Uma Sockalingam (2009)
Osteoporosis is a systematic skeletal disease characterised by a reduction of bone mineral density (BMD) and a disruption of bone micro-architecture, leading to enhanced bone fragility and a consequent increase in the risk of fracture, particularly of the spine, wrist and hip; the fracture occurs at the cancellous bone. The implications of osteoporosis include a reduction in the life expectancy and deterioration in the quality of life.